Menu Engeneering: application of Smith-Kasavana method in à la carte restaurant - Gularte, Cássio da Luz; Cardoso, Jaqueline de Fátima (Revista Turismo em Análise, 2020)
Menu engineering is a managerial tool for analyzing the relationship between sales price and popularity of the items that make up the menu, over a period of time, in businesses in the food industry outside the home. The purpose is to improve the existing menu, in terms of profitability and attractiveness. This work aims to apply and analyze the menu engineering in an à la carte restaurant, in order to show the importance of this tool as an instrument to support strategic decision in the food industry outside the home. The study proposes to use menu engineering according to the Smith-Kasavana protocol, in order to demonstrate the applicability of this instrument to support the decisions of managers in the sector, especially micro and small companies. A step-by-step approach for applying the tool to a small company was established and, based on data analysis, generic strategic actions applicable to establishments in the food industry outside the home recommended. This research contributed to the management of establishments in the food and beverage sector, demonstrating the application of the method, as well as the results that generate indications of promotional and strategic actions that, over time, will provide better results to establishments.